Trade competition measurement and the choice of measurement indexes - Dumitrescu, I. M.; Crespo, N.; Simões, N. (Studia Universitatis Babes-Bolyai Oeconomica, 2018)
The aim of this paper is to bring a methodological and empirical contribution to the measurement of trade competition. Globalization and the emergence of new poles in the world economy brought changes to the global landscape and consequent increase in international trade. There is a debate in the literature with regard the indexes that are better fit to be applied in empirical examples for the acquirement of relevant results for measurement of trade competition. This measurement will be achieved by observing the levels of structural similarity in distinct areas and at different moments in time. A higher degree of similarity between the export structures implies a stronger competition in destination markets. The values obtained for this measurement are highly relevant for the trade competition topic. Through this study we further explore the measurement of trade competition and comparatively discuss several indexes used in this area of research